Efficacy of manual acupuncture vs. placebo acupuncture for generalized anxiety disorder (GAD) in perimenopausal women: a randomized, single-blinded controlled trial - Liu, Xin; Li, Meichen; Xie, Xiaoyan; Li, Yingjia; Li, Keyi; Fan, Jingqi; He, Jun; Zhuang, Lixing (Frontiers in Psychiatry, 2023)
Background: Generalized anxiety disorder (GAD) is common among perimenopausal women. Acupuncture may be an effective treatment for GAD, but evidence is limited. The pathogenesis of GAD is not yet clear, but it is related to the hypothalamic-pituitary-adrenal axis and its excretion, cortisol (CORT) and adrenocorticotropic hormone (ACTH). The object of this study is to evaluate the efficacy of manual acupuncture (MA) versus placebo acupuncture (PA) for perimenopausal women with GAD. Methods: This study is a single-center, randomized, single-blind clinical trial conducted in the First Affiliated Hospital of Guangzhou University of Chinese Medicine. A total of 112 eligible GAD patients were randomly assigned (1:1) to receive MA (n=56) or PA (n=56) three times per week for four weeks. The primary outcome measure was the HAMA score. The secondary outcome measures were the GAD-7 and PSQI scores and the levels of CORT and ACTH. The evaluation will be executed at the baseline, 2 weeks, the end of the treatment and a follow-up 3-month period. Results: Significant improvements of HAMA (p < 0.001, η2 p = 0.465), GAD-7 (p < 0.001, η2 p= 0.359) and ACTH (p=0.050) were found in MA group compared to PA group between T0 and T2. No difference of PSQI (p = 0.613, η2 p= 0.011) and CORT (p=0.903) in the MA group compared to the PA group between T0 and T2. Long-term improvements of HAMA (p < 0.001, p < 0.001) was found in MA group and PA group. Conclusion: This study was the first completed study to evaluate the efficacy of acupuncture and placebo acupuncture for GAD in perimenopausal patients. Results suggested that placebo acupuncture has a therapeutic effect, however, acupuncture had a greater therapeutic effect than placebo acupuncture. This study supports the effectiveness of acupuncture and thereby contributes to extended treatment options for GAD. Trial registration: Chinese Clinical Trial Registry, ID: ChiCTR2100046604. Registered on 22 May 2021. URL: http://www.chictr.org.cn.